2009
DOI: 10.1097/bpo.0b013e3181b2bae7
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Application to the Growth Plate in the Rabbit: A New Potential Approach to Epiphysiodesis

Abstract: Radiofrequency has proved to be effective in producing growth arrest in rabbits with no complications. Technical improvements and adaptations may allow its use for pediatric limb inequalities or angular deformities in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
1
15
0
7
Order By: Relevance
“…15 In an animal study, growth plates treated with radiofrequency ablation at 60°C were seen to fuse. 16 As the heat of polymerisation of bone cement ranges from 60° to 80°C, 17 this could potentially damage an epiphysis, and appears to have done so in this case. We can find no other case document- Radiograph six months after the initial endoprosthetic replacement showing no growth from the remaining distal femur.…”
Section: Discussionmentioning
confidence: 84%
“…15 In an animal study, growth plates treated with radiofrequency ablation at 60°C were seen to fuse. 16 As the heat of polymerisation of bone cement ranges from 60° to 80°C, 17 this could potentially damage an epiphysis, and appears to have done so in this case. We can find no other case document- Radiograph six months after the initial endoprosthetic replacement showing no growth from the remaining distal femur.…”
Section: Discussionmentioning
confidence: 84%
“…In a study on rabbits using RFA, growth inhibition was achieved by radio-frequency coagulation of the physis (Ghanem et al 2009). Positive results in rabbit experiments have also been reported in 2 later studies (Moon et al 2012, Widmann et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous methods reduce length of hospital stay, operating time, and postoperative pain, and they result in minor surgical scars compared to open surgery. Based on experimental rabbit models (Ghanem et al 2009, Widmann et al 2010, Moon et al 2012), epiphysiodesis using radio-frequency ablation (RFA) is a successful minimally invasive method. However, this species behaves differently to humans when studying bone.…”
mentioning
confidence: 99%
“…The need for multiple centimetric incisions and subcutaneous implantation of an infusion pump, as well as the potential systemic effects, make this technique less appealing for clinical use. Inspired by the success of radio frequency in treating orthopedic conditions such as osteoid osteoma, the teams of Ghanem et al [60 ] and Widmann et al [61 ] recently reported its use for epiphysiodesis in rabbit models. Both studies showed radiological and histological evidence of complete growth arrest without any damage to the articular cartilage.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…The procedure would be performed on an outpatient basis under local anesthesia, allowing immediate weight-bearing and quick return to normal activities. However, further studies should evaluate application on larger animal models, determine adequate regimens of energy and delivery time in humans, and possibly identify a temperature range that would induce reversible transient growth arrest [60 ].…”
Section: Experimental Techniquesmentioning
confidence: 99%